CODE-SWITCHING AS A BRIDGE OR A BARRIER: A SOCIOLINGUISTIC ANALYSIS OF TEACHERS’ CODE-SWITCHING IN PAKISTANI CLASSROOMS (Contemporary Journal of Social Science Review, 2025)
The present study explored the influence of teachers’ code-switching on students’ perceptions and classroom engagement within the context of English as a Medium of Instruction (EMI) in Pakistan. A quantitative research design was employed with a sample of 203 undergraduate students, who completed standardized scales measuring their perceptions of teachers’ code-switching and their level of academic engagement. Reliability analysis confirmed acceptable to strong internal consistency across the instruments (α = .69–.86). Correlational findings indicated a moderate positive relationship between teachers’ code-switching and students’ favorable perceptions (r = .24, p < .01). Regression analysis further revealed that code-switching significantly predicted student engagement (β = .49, p < .001), explaining 23% of the variance. Group comparisons showed that students with lower English proficiency reported more benefits from teachers’ code-switching than those with higher proficiency, whereas gender differences were non-significant. A one-sample t-test indicated that teachers’ use of the first language did not significantly increase confusion among students. These findings suggest that purposeful and limited code-switching can be a valuable pedagogical strategy in EMI classrooms, particularly for learners with lower English proficiency. Implications for language policy and teacher training are also discussed.